Assessing the susceptibility of alpine soils to erosion using soil physical and site indicators. (4th July 2013) - Stanchi, S.; Freppaz, M.; Godone, D.; Zanini, E.
Abstract Soil erosion in mountainous regions is a key issue in land use planning, and this is particularly true in the Alps where intense anthropogenic influences at low elevations and abandonment in higher regions often coexist to affect soils. Natural hazard and risk assessment are essential given the density of settlements and associated facilities. Soil loss due to water erosion is very common and is becoming more frequent as a consequence of climate change which affects precipitation regimes, frequency of extreme meteorological events, snow melt and vegetation. In this study, we describe the production of a map showing susceptibility to soil erosion in the Aosta Valley (northwest Italian Alps). Most research on slope instability has focused on rock failures, but we investigated upper soil horizons by analysing chemical and physical properties, which could contribute to slope instability. The steps involved in creating the map are explained, and these involved GIS overlay, sampling, soil description, selection of relevant chemical and physical indicators of soil susceptibility to erosion, and overall erosion susceptibility assessment. The resultant indicator values correspond well with field observations to thus validate the methodology and demonstrate its usefulness in land use planning and management in Alpine areas.